2006
DOI: 10.1016/j.cardiores.2006.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin regulates NFAT-dependent iNOS expression and protection of cardiomyocytes: Co-operation with Src tyrosine kinase

Abstract: These results support a cardioprotective role for calcineurin mediated by NFAT-dependent induction of iNOS expression and co-operativity between calcineurin and Src.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…The regulation of the iNOS gene promoter by calcineurin has been reported (36). LPS-induced iNOS expression in the heart was abrogated by the pharmacological inhibition of calcineurin (36).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The regulation of the iNOS gene promoter by calcineurin has been reported (36). LPS-induced iNOS expression in the heart was abrogated by the pharmacological inhibition of calcineurin (36).…”
mentioning
confidence: 99%
“…heart block; sodium current; sudden death; inducible nitric oxide synthase; transgenic overexpression of calcineurin TRANSGENIC OVEREXPRESSION of constitutively active calcineurin (CN/Tg) in cardiac myocytes results in profound concentric hypertrophy followed by ventricular dilatation, interstitial fibrosis, heart failure, and eventually sudden cardiac death (13,26,32,33,40). The sudden deaths relate to ion channelopathies, which are downstream consequences of abnormalities of calcium homeostasis (17) and an inflammatory process (6, 10, 27, 36).Previous studies indicate that inducible nitric oxide (NO) synthase (iNOS) is a downstream target of calcineurin (12,19,36,44,45). The regulation of the iNOS gene promoter by calcineurin has been reported (36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that NF-κB predominantly regulates the expression level of iNOS proteins (30). However, it has also been reported that iNOS proteins are induced by the constitutive activation of calcineurin-NFAT signaling in cardiomyocytes (31). In accordance with this, the expression of a constitutively active mutant of NFAT (NFAT-CA) decreased AT 1 R-stimulated Ca 2+ response, which was completely abolished by the treatment with L-NAME or 1400W (Fig.…”
Section: P2ymentioning
confidence: 55%